Meluruskan Pola Pikir Umat Mengenai Keimanan Ahli Kitab dalam Alquran dan Implikasinya terhadap Toleransi Beragama - Abdul Munim Amaly; Munawwar Rahmat (Intizar, 2018)
When people say Ahli Kitab, the Muslims views tend to lead to infidels. But is that so? Is Ahli Kitab are infidels? Or are they believers? The purpose of this study is to explore the truth in the perspective of the Qur'an and its implications for religious tolerance. By using the method of "Digital Qur'an Thematically", each verse with the term of Ahli Kitab is analyzed. From the analysis of the verses of the Qur’an found 35 verses about the term of Ahli Kitab, including eight verses which state that the Ahli Kitab are infidels, and two verses declare some of the Ahli Kitab of Faith. This finding implies the implications of religious tolerance, namely mutual respect for one's faith, as exemplified by the Prophet Muhammad.